Mass and heat transfer in turbulent bed contractor by Fares T. Abdul-Hamid. - Abdul-Hamid, Fares T.
The coefficient of mass and heat transfer have been measured in a turbulent bed contactor. The turbulent bed contactor is a cylindrical column containing a low density solid spheres which are fluidized by upward flowing gas and irrigated by downward flowing liquid. Atmospheric air is used as the gas while hot water is used as the liquid.